The binding sites of miR-619-5p in the mRNAs of human and orthologous genes - Atambayeva, Shara; Labeit, Siegfried (BMC genomics, 2017)
BACKGROUND: Normally, one miRNA interacts with the mRNA of one gene. However, there are miRNAs that can bind to many mRNAs, and one mRNA can be the target of many miRNAs. This significantly complicates the study of the properties of miRNAs and their diagnostic and medical applications. RESULTS: The search of 2,750 human microRNAs (miRNAs) binding sites in 12,175 mRNAs of human genes using the MirTarget program has been completed. For the binding sites of the miR-619-5p the hybridization free energy of the bonds was equal to 100% of the maximum potential free energy. The mRNAs of 201 human genes have complete complementary binding sites of miR-619-5p in the 3'UTR (214 sites), CDS (3 sites), and 5'UTR (4 sites). The mRNAs of CATAD1, ICA1L, GK5, POLH, and PRR11 genes have six miR-619-5p binding sites, and the mRNAs of OPA3 and CYP20A1 genes have eight and ten binding sites, respectively. All of these miR-619-5p binding sites are located in the 3'UTRs. The miR-619-5p binding site in the 5'UTR of mRNA of human USP29 gene is found in the mRNAs of orthologous genes of primates. Binding sites of miR-619-5p in the coding regions of mRNAs of C8H8orf44, C8orf44, and ISY1 genes encode the WLMPVIP oligopeptide, which is present in the orthologous proteins. Binding sites of miR-619-5p in the mRNAs of transcription factor genes ZNF429 and ZNF429 encode the AHACNP oligopeptide in another reading frame. Binding sites of miR-619-5p in the 3'UTRs of all human target genes are also present in the 3'UTRs of orthologous genes of mammals. The completely complementary binding sites for miR-619-5p are conservative in the orthologous mammalian genes. CONCLUSIONS: The majority of miR-619-5p binding sites are located in the 3'UTRs but some genes have miRNA binding sites in the 5'UTRs of mRNAs. Several genes have binding sites for miRNAs in the CDSs that are read in different open reading frames. Identical nucleotide sequences of binding sites encode different amino acids in different proteins. The binding sites of miR-619-5p in 3'UTRs, 5'UTRs and CDSs are conservative in the orthologous mammalian genes.
Gesehen am 20.08.2018